Formation of civic identity of pedagogical college students - V. E. Mineev-Li; Yu. Shapovalova (Вестник Северо-Кавказского федерального университета)
The article discusses the features of the formation of the civic identity of students of the pedagogical college, their analysis is carried out. The main results of the study are the following: the civic identity of pedagogical college students can be formed within the framework of a number of activities: directly educational activities in the form of cycles of classes devoted to the formation of civic identity; long-term projects aimed at the formation of civic identity; activities within the framework of pedagogical practice. The author analyzes the existing approaches to the formation of the civic identity of youth in individual subjects of the federation; suggests a number of directions that allow students of pedagogical college to effectively form a civic identity; identifies prospects for further research in the field of the formation of the civic identity of modern Russian youth in general and students of pedagogical colleges in particular.